2014
DOI: 10.1016/j.contraception.2014.03.018
|View full text |Cite
|
Sign up to set email alerts
|

Different Pearl Indices in studies of hormonal contraceptives in the United States: impact of study population

Abstract: Objective To examine the impact of subject characteristics on efficacy as measured by the Pearl Index (PI) in clinical trials and to make study populations similar by matching. Methods Our analysis used US data from four large Phase III studies. We compared results from one fertility control patch study with pooled data from three studies with virtually identical design on oral hormonal contraceptives. First, we identified three characteristics that had the most impact on the PI. Second, we used these three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 16 publications
5
8
0
Order By: Relevance
“…Our post-hoc regression analysis indicated higher pregnancy rates for black and Hispanic women desiring pregnancy after the study. This finding reflects the conclusions of other investigators who have considered ethnicity, race, poverty level, and education relative to adherence in contraceptive clinical trials 24, 25, 26. One interpretation is that social and cultural challenges might affect adherence and reporting of contraceptive use, especially for black and Hispanic women considering future pregnancy 27 .…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Our post-hoc regression analysis indicated higher pregnancy rates for black and Hispanic women desiring pregnancy after the study. This finding reflects the conclusions of other investigators who have considered ethnicity, race, poverty level, and education relative to adherence in contraceptive clinical trials 24, 25, 26. One interpretation is that social and cultural challenges might affect adherence and reporting of contraceptive use, especially for black and Hispanic women considering future pregnancy 27 .…”
Section: Discussionsupporting
confidence: 81%
“…Our results also raise the methodological issue of obtaining accurate reports about contraceptive use during clinical trials and in real-life settings. Women in these trials used paper diaries to record information required for calculating pregnancy rates, which did not reveal between-group differences in adherence and highlight the challenges that investigators must confront when trying to show product efficacy in clinical trials 24, 25, 26, 27. Investigators need more innovative technologies and strategies for obtaining accurate information about participant motivation and behaviours in contraceptive trials, especially for user-controlled methods.…”
Section: Discussionmentioning
confidence: 99%
“…Pooling data from studies which suppressed sperm count to no more than 1 M/mL and calculating Poisson confidence limits, yields a contraceptive failure rate of 0.6 (0.3–1.1)%. This compares favorably with the use of the oral contraceptive pill by women in the first year 3537 . In fact, modern female hormonal methods, which utilize lower doses, report 12 month failure rates of 7% 36 .…”
Section: 2 Mhc Induces Predictable Contraceptionmentioning
confidence: 92%
“…In addition to these, Trussell and Portman concluded that changes in the [3] study population alone over time (e.g., with immigration, changes in marital status, contraception democratization) would decrease medication adherence [13•]. Gerlinger also noted a geographical difference between Europe and the USA, noting that the PI tends to be higher for the latter, but was unable to explain why [9]. Trussell and Portman in 2013, as well as Abascal in 2015, offered some explanation.…”
Section: Effectiveness Of Oral Contraceptives: the Pearl Indexmentioning
confidence: 95%
“…In 2014, Gerlinger compared, with a matching propensity score, four studies that included 6602 subjects [9] (one with a contraceptive patch, for which the PI was 3,56 and three other COC studies with respective PIs of 0,72 [10]), 0,79 [11]) and 1,65 [12]). They identified three variables which had an important impact on the rising Pearl Index: to report Hispanic ethnicity, to have previously been pregnant, and to have rarely used effective hormonal contraception in the past [9]. In addition to these, Trussell and Portman concluded that changes in the [3] study population alone over time (e.g., with immigration, changes in marital status, contraception democratization) would decrease medication adherence [13•].…”
Section: Effectiveness Of Oral Contraceptives: the Pearl Indexmentioning
confidence: 99%